PENGARUH LIKUIDITAS, AKTIVITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR KABEL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lase, Agustian Zisokhi; Jubi, Jubi; Susanti, Elly; Putri, Debi Eka (SULTANIST: Jurnal Manajemen dan Keuangan, 2019)
The objectives of this research are 1. Identify the liquidity, activity, profitability and value of sub sector cable company listed on Indonesian stock exchange. 2. Identify the liquidity, activity, profitability effect to the value of sub sector cable company listed on Indonesian stock exchange simultaneously or partially. This research was done by using the method of qualitative descriptive and quantitative descriptive analysis. The objectives this research used sub sector cable company listed on Indonesian stock exchange. The data was collected by using documentation method. The analytical techniques used are classical assumption test, multiple linear analysis, correlation coefficientÂ  determination coefficient and hypothesis test.The result of multiple linear regression test had a negative effect to the value of the company. The results of the correlation coefficient and correlation determination analysis concluded that liquidity, activity, and profitability, have a strong connection with the company value and influenced by another variable. Simultaneous test results obtained that liquidity, activity, and profitability influence don't have a significant effect to the company value.This research suggests that the company should increase sale, accelerate debt collection, minimize operational cost and stabilize dividend development to the investor, so it can increase the company profitsÂ Keywords : Liquidity, Activity, Profitability and Company Value